Gene mutation effect of aqueous and methanol extracts of salted fish from Pulau Pinang, Malaysia towards V79 lung fibroblast cells - Ahmad Rohi Ghazali; Rasyidah Mohamad Halim; Nor Fadilah Rajab; Noorain Ramli; Rozaini Abdullah; Firdaus Kamarulzaman; Zaliha Harun (Universiti Kebangsaan Malaysia, 2013)
Salted fish is a locally processed raw food which is used in everyday cooking among Malaysians. Previous studies suggested that salted fish intake was a risk of nasopharyngeal cancer. Hence, this study was carried out to evaluate gene mutation effects through the induction of mutagenic effect of aqueous and methanol extracts of salted fish from Balik Pulau, Pulau Pinang, Malaysia. Balik Pulau was chosen for sampling purpose due to its popularity as a commercial centre for local raw fisheries in Malaysia. Evaluation of mutagenic effect was carried out by hprt Gene Mutation Assay towards V79 lung fibroblast cells. It was found that the aqueous and methanol extracts of salted fish were not cytotoxic towards V79 lung fibroblast cells. It was also found that the extracts of salted fish from Balik Pulau were not mutagenic towards hprt gene of V79 lung fibroblast cells as the mutation frequency of the extracts did not exceed 3 times of the value for negative control mutation frequency. In conclusion, both aqueous and methanol extracts of salted fish from Balik Pulau did not have gene mutation effect towards hprt gene in vitro. However, other toxicological profile could be assessed to determine the mechanism of toxicity of salted fish.